HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PASIEN STROKE DALAM MELAKUKAN FISIOTERAPI DI RSUD H. SAHUDIN KUTACANE TAHUN 2021 - Dina Andriani (Universitas Prima Indonesia, 2021)
Family support is the help provided by the family to family members in need when facing problems whereas compliance is the extent to which the patient's behavior is in accordance with the provisions provided by the health professional. The design of this study is correlational. The goal is to find out the relationship of family support with the compliance of stroke patients in doing physiotherapy. Sampling using purposive sampling technique amounted to 22 respondents who were a family of stroke patients who did physiotherapy at RSUD Kutacane, Southeast Aceh Regency. The compliance rate of stroke patients in doing physiotherapy in the hospital is about 72.7% where families who provide support as much as 77.3%. Based on the results of the analysis with fisher's exact test obtained the value P (fisher) = 0.000. Then there is a relationship between family support and the compliance of stroke patients in doing physiotherapy. These results show that if the family provides good support, then the patient's compliance with physiotherapy will be better as well. Based on the results of this study, the family should be able to provide support to patients. It is expected that the H. Sahudin of Southeast Aceh Regency Hospital, Educational Institutions and other related institutions will develop a permanent procedure on providing health education to patients and their families, especially about the importance of family support in the recovery of the patient's health.